DIFFERENCE OF WORK SATISFACTION ON TEACHERS BASED ON GENDER LEADERSHIP - Susi Endang Era Wati; Suparno Suparno; Rosana Dewi Yunita (Jurnal Psikologi, 2007)
The aim of this research is to know the difference of work satisfaction based on gender leadership. The participants of this research is 48 teachers from SMP Negeri 2 Kartasura and SMP Negeri 3 Kartasura. The result of this research shows t-test about 3,348 (p < 0.01). It tells us about the difference of work satisfaction based on gender leadership which is the empiric mean for male leadership around 143,652 and for female leadership around 128,990. This result shows that teacher work satisfaction who had male leadership is higher than who had female leadership.Key words: gender in leadership, work satisfaction